Pengetahuan dan Praktik Pemberantasan Sarang Nyamuk Terhadap Tempat Perindukan Vektor DBD - Fitra Hidayat; Noraida Noraida (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2019)
Abstract: Knowledge and Practices of Eradicating Mosquito Nests against DHF Vector Breeding Sites. The Puskesmas Banjarbaru Utara includes the Mentaos and Loktabat Utara Urban Villages. From year to year the two urban villages always have DHF cases repeatedly. The purpose of this study was to determine the relationship between knowledge and practice of eradicating mosquito nests against DHF vector breeding sites in the Puskesmas Banjarbaru Utara. This study is an analytical study with cross-sectional design. The sample in the study were 99 family heads. The study was conducted in November 2018 until January 2019. Data were analyzed using the chi-square test. The results showed that there was a relationship between knowledge of mosquito nest eradication and DHF vector breeding sites because of the value of p (0.002) < α (0.05) and there was also a relationship between the practice of eradicating mosquito nests and vector breeding sites because of the p (0.000) < α (0.05).